Child Delinquency on the Internet - Abd Rahman Shah, Hendun; Abdul Shukor, Syahirah; Mohamad Ali, Norfadhilah; Abdul Ghafar, Abidah; Mohammad Ahmad, Nisar; Yusof, Nabilah; Atira Musa, Nurul (International Journal of Engineering and Technology, 2018)
Recent reported cases and news on children and the Internet reflect the vulnerability of children when they are online, especially with in using the new medium of social networking websites such as Facebook, Instagram, and Twitter. The criminal justice system faces the dilemma when children break the law, as children are considered as minors who are not legally responsible for their actions. In most cases, the society tend to focus on protecting children from neglect, abuse or harms but often overlooked of protecting children who are involved in harming or causing injury to other people or cause damage to property. It is equally important to address the growing concern on childrenâ€™s exposure to usage of the Internet. Thus, the question such as, can the childâ€™s wrongs on the Internet be considered as a delinquent act, namely possible wrongful acts conducted by children that would otherwise be an offence if committed by an adult, is explored. The legal status and minimum age of criminal responsibility in Malaysia are also examined. In addition, the Shariah views will be discussed briefly. Then, the paper explores the problems and challenges face by children in using social media websites. Finally, the paper suggests that the government and the community in particular parents and teachers have vital roles to play in ensuring that the policies and rules provide mechanism not only to protect children but also to empower them as a citizen of the country. This may be done by advocating legal awareness and educating the children to be more responsible in their acts online and uphold respect in law, ethics and morality. Â Â Â